O betão armado em Portugal, através dos arquitectos - Ana Filipa Pinto Machado Namora Monteiro (2015)
This research seeks to analyze and relate all the elements that, in the early twentieth century, influenced and led the Portuguese architects to project architectural work where the concrete has a visual Impact. In the "Introduction" it is intended, as required, to identify the object of study of this work, its aim, explain the methodology used for the composition of this work and, finally, cite key documentary sources for its realization. In this context, this work is divided in two parts. Part 1 it is subordinated to two themes - "Reinforced Concrete in Time" and "The Evolution of Reinforced Concrete from the nineteenth to the twentieth." The first theme is constituted by two chapters, which initially intended to make a note of the first steps towards achieving the concrete being the embryonic source of this material France and England. The second chapter analyzes, individually, the use of reinforced concrete, through foreign pioneers who caught the attention of Portuguese architects. In the second theme, it is developed the third chapter which contextualize the cultural and socio-political landscape of the time, in parallel with the emergence of new architectural ambitions; Here, it is given special attention to the Exposition des Arts Decoratifs et Industriels Moderns, 1925, believed to serve as a hinge point for a new, modern image of Portugal. Part II develops the theme "The Path of Reinforced Concrete in the Portuguese Architects Hands", set in a fourth chapter. Here are four selected architects, Marques da Silva, Cristino da Silva, Cassiano Branco and Pardal Monteiro, from two different generations. Through them and their masterpieces it is verified the way concrete broke out in Portugal and became remarkable, breaking traditions and creating a new form of architectural expression. Finally, some final thoughts are made that claim to list the most important elements discussed in this work.